Supporting parents : improving outcomes for children, families and communities - Miller, Sue, 1956- (McGraw-Hill/Open University Press, 2010)
This book looks at the importance of supporting parents and explores some of the tensions that have emerged over the years in seeking to establish timely support for parents.